PERANCANGAN CONVEYOR MELALUI MODIFIKASI LUBRICANT CATRIDGE SEBAGAI PELUMAS OTOMATIS - Putu Oka Sutrisna; I Gusti Ngurah Adia Atmika (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2022)
Starting from a problem in the process of lubricating the conveyor motor using a grease gun manually which is done manually, so there will always be grease/lubricant overflow which is finally wiped using a cloth cloth. The rags that have been contaminated by this grease will become B3 Waste (Hazardous and Toxic Waste) which will be high. The lack of automatic equipment facilities requires employees to perform manual processing, this of course causes productivity and product quality to be less than optimal. Conveyor designer through modification of lubricant cartridge as automatic lubricant. Modify the lubricant cartridge so that it is able to lubricate automatically with a timer. Thus, the lubrication process for the motor conveyor axle can be carried out with precision and order, so that there is no longer any spillage of grease/lubricant that must be wiped with a cloth. This can eliminate one of the sources of B3 Lap Majun waste. This resulted in a decrease in the overall B3 Waste Load. With this system, it can reduce the burden of Hazardous and Toxic Waste, especially from contaminated cloth, by 0.04 tons/year.